Relationship between side medicine-ball throw performance and physical ability for male and female athletes - Ikeda, Y.; Kijima, K.; Kawabata, K.; Fuchimoto, T.; Ito, A. (European Journal of Applied Physiology, 2007)
The purpose of the study was to examine the factors contributing to performance of a side medicine-ball throw (S-MBT) and a fast side medicine-ball throw (FS-MBT) and to analyze some of the factors which account for the difference in side medicine ball throw performance between the sexes. Sixteen males and ten females were evaluated by S-MBT, FS-MBT, isometric maximal trunk rotation torque (IMTRT), One repetition maximum of Parallel Squat (1RMPS) and Bench Press (1RMBP), Bench Press peak power (BPPP), Static Squat Jump peak power (SSJPP) and vertical jump height. Males demonstrated significantly greater scores than females in all measurements. Significant correlations were observed in males, but not in females, between the distances during S-MBT and the IMTRT values (r = 0.596-0.739, P < 0.05-0.01) and the 1RMPS values (r = 0.683-0.725, P < 0.01). In FS-MBT performance, significant correlations were observed in males, but not in females, between the ball velocity values during FS-MBT and the IMTRT values (r = 0.611-0.687, P < 0.05-0.01), 1RMBP values (r = 0.596-0.655, P < 0.05-0.01) and 1RMPS values (r = 0.679-0.718, P < 0.01). These results suggested that the contributing factors of S-MBT and FS-MBT performance were deferent in males and females. Hence, the side medicine-ball throw test would be useful to examine the trunk rotation power of male athletes, but may have a limited potential as a predictor of trunk rotation power for female athletes.